Enhancing the Hydrodeoxygenation and Isomerization using Re Nanoparticles Decorated on Ni/SAPO‐11 Catalysts for Direct Production of Low‐Cold Flow Diesel from Triglycerides - Jirawat Chuseang; Vorranutch Itthibenchapong; Atthapon Srifa; Wanichaya Praikaew; Soontorn Tuntithavornwat; Bunyarat Rungtaweevoranit; Sakhon Ratchahat; Wanida Koo-amornpattana; Wantana Klysubun; Apiluck Eiad‐ua; Worapon Kiatkittipong; Suttichai Assabumrungrat (ChemCatChem, 2023)
Abstract The novel bifunctional Ni−Re supported on bimodal SAPO‐11 catalyst was designed for an economically combined process of direct triglycerides hydro‐deoxygenation and isomerization into low‐cold flow diesel. The catalyst with a Ni to Re molar ratio of 1 : 0.12 exhibited superior performance for diesel production containing large fraction of iso‐alkanes in comparison to Ni and Re benchmarks. Comprehensive characterizations revealed that the detection of Ni and Re co‐existed with NiO and ReO x on SAPO‐11 after the reduction confirmed by XRD, XANES, and XPS analysis gave a large distribution of Lewis acid sites (>80 %) noticed by Pyridine‐DRIFTS measurement. Under investigations of WHSV, reaction temperature, and H 2 pressure, the NiRe 0.12 catalyst contributed a nearly theoretical 77.1 % liquid yield, accompanied by a 18.2 % jet‐range and 52.1 % diesel‐range yields with a classification for 46.8 % iso‐alkanes and 23.5 % normal alkanes yields; whereas, the cold‐flow properties of liquid product were in the ranges of winter diesel standard. It was remarkably noticed that the combination effects of Ni and nanosized Re species substantially improved the diesel production comprising iso‐alkanes components with proper catalyst lifetime and low carbon deposition attributing to the fabricated active metal species on bimodal SAPO‐11 features with large distribution of Lewis acidic sites.
Keywords: Catalysis and Hydrodesulfurization Studies; Catalytic Processes in Materials Science; Catalysis and Oxidation Reactions